Sustainable Urban Mobility Plan and the electric mobility challenge. First results of the planning process in Genoa (IT) - Delponte, Ilaria (TeMA - Journal of Land Use, Mobility and Environment, 2021)
An increased use of local public transport (LPT) is often proposed as an essential contribution to the overall response to the environmental challenges. The major changes in the urban layout are accompanied by an adaptation of the infrastructural settings, necessary so that the movements can take place quickly, safely and efficiently, following to the main exigencies of its citizens. For this purpose, in accordance with the European Directive 2014/94 on alternative fuels, in Italy, the coordinated action at national level supports electricity and other fuels (such as liquefied and compressed natural gas and hydrogen) as priority fields of interventions for the entire supply of the transportation sector. Aware of the current state of Italian urban mobility, in August 2017 the Ministry of Infrastructure and Transport (MIT) introduced a planning tool dedicated to the 14 Metropolitan Cities, the Sustainable Urban Mobility Plan (SUMP) with the crucial objective of the electrification of “Rapid Mass Transport - TRM" systems. In particular, only TRM interventions that create a zero-emission are eligible for funding. Precisely in relation to sustainable electric mobility, this contribution deals with the step-wise project of new 4 trolleybus lines in Genoa, as an initial application of metropolitan TRM systems in Italy. In the paper, author provides the assessment of the electrification project adopted in Genoa and also first results from the case-study planning process.